Dielectric properties of BaTiO3 ceramics prepared from powders with bimodal distribution - Deshpande, S. B.; Potdar, H. S.; Patil, M. M.; Deshpande, V. V.; Khollam, Y. B. (Journal of Industrial and Engineering Chemistry, 2006)
BaTiO3 (BT) powders having bimodal distribution were synthesized successfully through a simple classical solid-state reaction route using cheap BaCO3 and TiO2 as starting materials. These powders were further processed in the form of green pellets to obtain dense BT ceramics having densities of similar to 94 similar to 96 % after sintering in air at 1350 and 1400 degrees C/4 h in air. The room temperature dielectric constant (epsilon(RT)) of similar to 1500 at 1 KHz frequency was increased to : 10000 at a Curie temperature (T-C) similar to 126 degrees C, showing a very sharp transition from a polar tetragonal to a non-polar cubic structure. The dielectric loss factor (tan 6) was similar to 1.5 %. SEM studies revealed the presence of dense microstructures having a distribution of smaller grains (size: 2 similar to 3 gm) surrounded by larger grains (>= 35 mu m). The ferroelectric hysteresis loop measurements on these samples gave values of spontaneous polarization (P-s) of similar to 12.0 mu C/cm(2), a coercive field (E-C) of similar to 2 similar to 2.5 kV/cm, and a dielectric strength (E-b) of similar to 48.0 kV/cm. DC-resistivity as high as 1.5 x 10(9) Omega-cm was obtained in these samples. All these results are quite comparable with reported ferroelectric/dielectric data and are discussed elaborately in this paper.
Keywords: BaTiO3; dielectric-ferroelectric properties; Microstructure; Sintering; stoichiometry

Electrochromic device (ECD) cell characterization on electron beam evaporated MoO3 films by intercalating/deintercalating the H+ ions - Sivakumar, R.; Gopinath, Chinnakonda S.; Jayachandran, M.; Sanjeeviraja, C. (Current Applied Physics, 2007)
Thin films of molybdenum oxide (MoO3) is one of the most interesting layered intercalation materials because of its excellent application in solid state batteries, large-area window and display systems. In recent years there has been considerable interest in variable transmittance electrochromic devices (ECD) based on Li+, H+ and K+ intercalation in transition metal oxide (MoO3) thin films. In the present investigation, thin films of MoO3 were prepared by electron beam evaporation technique on microscopic glass and fluorine doped tin oxide (FTO) coated glass substrates for the application in electrochromic device cells. The compositional stoichiometry of the films was studied by X-ray photoelectron spectroscopy (XPS). The electrochromic nature of the films has been analyzed by inserting H+ ions from the H2SO4 electrolyte solution using the cyclic-voltammetry (CV) technique. We studied the electrochromic device cells (ECD) incorporating an evaporated MoO3 thin films as electrochromic layers. The devices exhibit good optical properties with low transmittance values in the colored state, which make them suitable for large-area window applications. The maximum coloration efficiency of the cell was observed at about 70 cm(2)/c. (c) 2005 Published by Elsevier B.V.
Keywords: coloration efficiency; electrochromic device cells; molybdenum oxide thin films; optical density; stoichiometry

Interdigitated flow field impact on mass transport and electrochemical reaction in high-temperature polymer electrolyte fuel cell - Agarwal, Harshal; Thosar, Aniket U.; Bhat, Santoshkumar D.; Lele, Ashish K. (Journal of Power Sources, 2022)
The enhanced performance of Polybenzimidazole (PBI) based high-temperature polymer electrolyte fuel cell (HT-PEFC) with interdigitated flow field over the other flow fields can be a consequence of higher average pressure developed on the flow field due to dead end in the channels or faster mass transport due to pressuredriven convection in the gas diffusion layer (GDL). In the present study, the effect of average pressure on the flow field and mass transport mechanism in the GDL on the HT-PEFC performance have been systematically decoupled. Three-dimensional simulation validated by experimental studies confirm that the enhanced performance in case of the interdigitated flow field is due to faster mass transport in the GDL and not due to higher average gas pressure. The simulation studies are performed on the interdigitated flow field and compared against the parallel flow field to have an insight into the effect of key operating and geometric parameters. There exists an optimum value for channel to rib ratio and current density saturates after an air stoichiometry of 4 which is validated by experiments.
Keywords: HT-PEFC; Interdigitated flow field; Mass transport mechanism; pressure; stoichiometry